2015
DOI: 10.1038/pr.2015.63
|View full text |Cite
|
Sign up to set email alerts
|

Heparin-binding EGF-like growth factor and enteric neural stem cell transplantation in the prevention of experimental necrotizing enterocolitis in mice

Abstract: BackgroundNecrotizing enterocolitis (NEC) is associated with loss of neurons and glial cells in the enteric nervous system (ENS). Our goal was to determine whether enteric neural stem cell (NSC) transplantation, in conjunction with heparin binding-epidermal growth factor-like growth factor (HB-EGF), could protect against experimental NEC.MethodsIn vitro, HB-EGF effect on NSC proliferation and migration, and the receptors utilized by HB-EGF to exert these effects, were determined. In vivo, mouse pups were expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 27 publications
1
39
0
1
Order By: Relevance
“…In addition, the current studies exclusively examined exosomes derived from BM-MSC. We have previously shown that neural stem cells (NSC) can also protect the intestines from NEC [38]. Future studies will examine the efficacy of exosomes derived from different types of stem cells, including NSC and amniotic fluid (AF)-derived MSC.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the current studies exclusively examined exosomes derived from BM-MSC. We have previously shown that neural stem cells (NSC) can also protect the intestines from NEC [38]. Future studies will examine the efficacy of exosomes derived from different types of stem cells, including NSC and amniotic fluid (AF)-derived MSC.…”
Section: Discussionmentioning
confidence: 99%
“…(6, 1719) Intestine from duodenum to ileum was harvested, opened longitudinally, and the mucosa and submucosa stripped away. The muscular layer was digested in DMEM/F12 containing 1mg/mL Collagenase and 1mg/mL Dispase (Worthington Biochemical Corporation, Lakewood, NJ) for 45 – 60 min.…”
Section: Methodsmentioning
confidence: 99%
“…The model of NEC was based on that described by Barlow et al . (6, 7, 2023) Rat pups delivered via C-section one half-day prematurely were randomized into six groups: (1) breastfed ( n = 10 ); (2) NEC + 1% phosphate-buffered saline (PBS, Corning, Manassas, VA) ( n = 62 ); (3) NEC + AF-MSC ( n = 42 ); (4) NEC + AF-NSC ( n = 37 ); (5) NEC + BM-MSC ( n = 48 ); (6) NEC + E-NSC ( n = 36 ). After delivery, each pup received a single intraperitoneal (IP) injection of 2×10 6 SC in 0.1mL PBS.…”
Section: Methodsmentioning
confidence: 99%
“…Recent evidence from 3 different research groups has suggested that stem cells are able to influence the course of the disease in experimental NEC [88]: amniotic fluid stem (AFS) cells [89], mesenchymal stem cells [90,91], and enteric neural stem system cells [92]. In addition to the beneficial effects of AFS cells and the conditioned medium from AFS cells, other recent evidence highlights the potential role of factors in amniotic fluid in the prevention and/or treatment of NEC.…”
Section: Preventionmentioning
confidence: 99%